SISTEM INFORMASI SISA SEDIAAN KAYU PADA PERUM PERHUTANI KABUPATEN NGANJUK BERBASIS WEB - Maya Galuh Setiyaningrum; Dinny Wahyu Widarti (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2024)
Perum Perhutani is a public company under the state forest department whose function processing of forest products and forest plants, the results of which are teak forest. Teak wood that has been cut from the forest is done manually recording is recording in the book and then placed in Tempat Penimbunan Kayu (TPK).Recording in the book make employees Perhutani office running out of time, so Perhutanioffice intend to improve the information system for the better. From the results of the analysis showed that the manual system of registration in the book requires a computer-based process and the manual system it is proposed to build a computer-based information systems.